"Our Lands are Our Lives": Gendered Experiences of Resistance to Land Grabbing in Rural Cambodia. Issue 4 (2nd October 2019) - Park, Clara Mi Young
ABSTRACT: Cambodia is known as a hotspot for land grabbing in Southeast Asia. Land dispossession due to elite capture, natural resources exploitation, and agribusiness development has catalyzed international attention following outbreaks of violence, mass protests, and retaliations. Agrarian economies, as well as social and gender relations and thus power dynamics at different levels, are being transformed and reshaped, facilitated by policies that promote capital penetration in rural areas and individualization of land access. Focusing on cases of rural dispossession and political resistance in Ratanakiri and Kampong Speu provinces, and drawing on reports, government documents, focus group discussions, and interviews, this study analyzes the gendered implications of land grabbing in contemporary Cambodia and argues that gender shapes and informs women's responses and politics, as well as the spaces in which these are played out.